ZAT BESI DI PENDONOR TERATUR DAN YANG TIDAK TERATUR (Iron in Regular and NonRegular Donors) - Irna Diyana Kartika; Lince Wijoyo; Syahraswati Syahraswati; Rachmawati Muhiddin; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Blood donation is a process of taking blood from someone, either voluntarily or as a replacement donor blood banked for later usein blood transfusions. Regular donors are donors who regularly donate blood between 3−4 times a year. Nonregular donors are thosewho do not routinely donate blood in a year. Each donor donating one bag of blood, suffered a loss of approximately 200 mg of iron.The purpose of this study was to know the differences in the levels of iron profiles in regular and nonregular donors. The study wasconducted cross sectional on 65 samples of blood from the UPTD Transfusi Darah South Sulawesi Provincial Health Office, consisting of34 regular donors and 31 nonregular donors. Serum iron and TIBC levels were examined using ABX Pentra 400 with colorimetric andimmunoturbidimetry method. Ferritin level was examined using Elecsys with ECLIA principle. The data were then analyzed by unpairedT test. In this study, the regular donors showed an average serum iron level of 87.09 μg/dL, TIBC level 255.41 μg/dL and ferritin level121.27 μg/dL. The nonregular donors, showed an average serum iron level of 83.26 μg/dL, TIBC level was 261.80 μg/dL and ferritinlevel was 158.62 μg/dL. The results showed no significant differences between the levels of iron profiles in regular and nonregulardonors. Based on this study, it can be concluded that regular and nonregular blood donation did not affect the levels of iron profiles. Itis recommended to conduct a further cohort research to know the levels of iron profiles in blood donors by comparing before and afterdonating blood.